Hygric performance of new building components for vertical green gardens - Pavel Kopecký (Acta Polytechnica CTU Proceedings)
The newly developed box-like panel lightweight element for vertical greenery was designed and built at University Centre for Energy Efficient Buildings of the Czech Technical University in 2020. A test site for testing green facade components is operated since spring 2021. Test samples differ in shape, arrangement of functional layers, water distribution means and irrigation patterns. The article presents and discusses measured data at selected test samples during growing season in year 2021. Physical quantities, such as surface temperature of plants, moisture content and matric potential of growing substrate, water inflow and outflow, and ambient boundary conditions, were recorded.